Long-Term Dynamics of HIV-Infected Mortality and Risk Factors of the Lethal Outcome in the Presence and Absence of Concomitant Tuberculosis - V. I. Sergevnin; O. V. Tukacheva; O. E. Mikova; M. V. Rozhkova (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. The mortality rate of patients with HIV infection, including concomitant tuberculosis (HIV/TB), continues to increase. The goal of the work is to study the longterm dynamics of HIVinfected mortality and risk factors of the lethal outcome in the presence and absence of concomitant tuberculosis.Materials and methods. An assessment of the mortality rates of HIV-infected people among the population of the Perm Region during the period from 2005 (the year of registration of the first cases of HIV/TB) to 2021 was carried out. In order to determine the life expectancy of patients and risk factors of the lethal outcome the analysis of 414 outpatient records of HIVinfected people who died in 2021 was carried out. The degree of immunodeficiency and viral load in patients was taken into account based on the results of examinations conducted in the period 6 months before the lethal outcome.Results. During the 15year period of registration of the incidence of HIV/TB in the study area, 57.0% of those who died from causes directly related to HIV infection had TB. At the same time, despite the decrease in mortality from monotuberculous infection as a result of a decrease in the incidence of TB, in recent years there has been an increase in mortality from HIV/TB due to the intensification of the epidemic process of HIV infection. The average life expectancy of HIV-infected people who died directly from HIV infection in the absence of TB was 6.7 ± 0.3 years, with concomitant TB 5.7 ± 0.3 years. The lethal outcome of patients with HIV infection in the presence of TB and without TB was most often recorded with the number of CD4 + < 200 cells /ml and viral load > 100,000 copies /MBNA of HIV. At the same time, immunosuppression in deceased HIV/TB patients was more pronounced than in HIV-infected patients in the absence of TB.